(untitled) (Revista de Cultura e Extensão USP, 2017)
This article aims at delimiting the specificities of teaching, research and extension activities in higher education, based on the thought of the Brazilian educator Dermeval Saviani, and on writings associated with his historical-critical pedagogy. Such activities are related to the mottoes “reproducing knowledge to preserve culture” (teaching), “producing knowledge to enlarge culture” (research) and “communicating knowledge to (re)produce it” (extension). Based on these mottoes, the interrelations between the three activities are explored, highlighting the bidirectional role of extension as a relationship that seeks to strengthen both the university and the community it is part of, by means of the dialectic relationship between erudite and popular culture.